2021
DOI: 10.3390/molecules26206171
|View full text |Cite
|
Sign up to set email alerts
|

Marine Brominated Tyrosine Alkaloids as Promising Inhibitors of SARS-CoV-2

Abstract: There have been more than 150 million confirmed cases of SARS-CoV-2 since the beginning of the pandemic in 2019. By June 2021, the mortality from such infections approached 3.9 million people. Despite the availability of a number of vaccines which provide protection against this virus, the evolution of new viral variants, inconsistent availability of the vaccine around the world, and vaccine hesitancy, in some countries, makes it unreasonable to rely on mass vaccination alone to combat this pandemic. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…However, no favorable binding poses could be obtained for this compound using Glide SP, potentially indicating an inefficient interaction with the FABP . Likewise, although Psammaplysene D has been described to interact with some FABP residues (Ser373, Phe374), no favorable binding poses could be obtained using the Glide SP docking tool. , In the case of Psammaplysene D, the failure to obtain docking poses could be due to the larger size of the molecule, with a molecular weight of 783.2 g/mol, significantly surpassing confirmed ligands and likely not fitting the pocket properly. As for asiatic acid, taking into account the binding predicted for dexamethasone and bile acid derivatives, the absence of docking poses obtained is unexpected.…”
Section: Resultsmentioning
confidence: 99%
“…However, no favorable binding poses could be obtained for this compound using Glide SP, potentially indicating an inefficient interaction with the FABP . Likewise, although Psammaplysene D has been described to interact with some FABP residues (Ser373, Phe374), no favorable binding poses could be obtained using the Glide SP docking tool. , In the case of Psammaplysene D, the failure to obtain docking poses could be due to the larger size of the molecule, with a molecular weight of 783.2 g/mol, significantly surpassing confirmed ligands and likely not fitting the pocket properly. As for asiatic acid, taking into account the binding predicted for dexamethasone and bile acid derivatives, the absence of docking poses obtained is unexpected.…”
Section: Resultsmentioning
confidence: 99%
“…Plants have provided a promising alternative production platform for both natural bioactive compounds and recombinant therapeutics [ 31 ]. Plants naturally produce a diverse range of bioactive small molecules, such as alkaloids [ 32 ], flavonoids [ 33 ], terpenoids [ 34 ], and phenolic compounds [ 35 ], which are the source of countless pharmaceutical compounds for treating various diseases. Many bioactive compounds from medicinal plants, for example, those extracted from Artemisia annua L., Curcuma longa and Tripterygium wilfordii have been demonstrated to exhibit significant activities against SARS-CoV-2 through interfering with every step of the interaction of the virus with its host cells [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID‐19 pandemic, several herbal compound databases derived from the medicinal plants of various geographical regions, such as China, [65,69,73–76] India, [68,77] Vietnam, [78] Korea, [65] Jordan, [79] Africa, [80] and Brazil [81] have been evaluated, both computationally and experimentally, for their potential antiviral activities against the SARS‐CoV‐2. Accordingly, it has been reported that multiple phytochemicals from various compound classes, including polyphenols, [55,60,62–63,68,78,82–84] alkaloids, [57,63,66–69,85] terpenes [55,63,66–67,69,84,86] and flavonoids [9,55,60,63,66–69,71,76,82–84,87] show a striking antiviral activity against the virus.…”
Section: Introductionmentioning
confidence: 99%